Memoirs about his Holiness Patriarch Tikhon. Publication from the archive of M.E. Gubonin - Natalia Krivosheeva; Olga Kosik (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви, 2025)
The unique memoirs about Patriarch Tikhon published below, belonging to the outstanding historian Mikhail Efimovich Gubonin, as well as recorded by him from the words of his closest relatives and literarily processed, were included in the collection "Contemporaries about Patriarch Tikhon", designed in the form of three typewritten volumes. Most of the manuscript has been published . Mikhail Efimovich, who at one time was the subdeacon of Bishop Peter (Rudnev), more than once attended the divine services of His Holiness Patriarch Tikhon and greatly revered him. Already in these years Gubonin began to collect church documents, which was the beginning of the creation of a scientific and historical archive. Below are unpublished essays submitted to the university by the historian's widow Zoya Petrovna Gubonina. The memoirs depict people who came into contact with the Patriarch, as well as various situations related to His Holiness, which enliven the historical context of his life. The memoirs reveal to the reader the complex, dramatic world of church life in the post-revolutionary years, the moods and interests of church people of that era. Currently, work is continuing on the remaining part of the manuscript.